NILAI-NILAI KONSELING PADA TRADISI TARI SEBLANG SUKU OSING BANYUWANGI - Siti Ulfiyani; Hanik Mufaridah (Maddah : Jurnal Komunikasi dan Konseling Islam, 2023)
The traditional Seblang dance ritual is a traditional ceremony held in the form of dance accompanied by gamelan and a choir. Seblang stands for before ilang or “loss of consciousness”. The Seblang ritual is performed to clean the village and repel reinforcements, so that the village remains safe and peaceful with a dancer from among a girl who is 10 years old or has not menstruated and is in a condition where a dancer is possessed by an ancestral spirit. The Seblang dance tradition is held during the Shawwal month or to be precise on the third or fourth day after the Eid al-Fitr holiday for one week. The dancers in the Seblang dance ritual are not random people, dancers must come from their ancestral lineage. The value of counseling is a belief that can provide positive value from a person’s point of view in which it can provide a change in accordance with what they see around them. The discussion referred to in this study is to determine the values of counseling in the Seblang dance tradition of the Osing Banyuwangi tribe. This study aims to describe what processions are carried out when carrying out the Seblang dance ritual and explore counseling values in the Seblang dance tradition in the village of Bysari, the Osing tribe of Banyuwangi. The research method used in this research is ethnographic qualitative. The results of the study can be concluded that counseling values in the Seblang dance tradition of the Osing Banyuwangi tribe provide positive values and provide lessons in dealing with social life, namely having spiritual values, values for oneself, and muamalah (social) values.